2013
DOI: 10.1186/1471-2164-14-770
|View full text |Cite
|
Sign up to set email alerts
|

The periodontal pathogen Porphyromonas gingivalis changes the gene expression in vascular smooth muscle cells involving the TGFbeta/Notch signalling pathway and increased cell proliferation

Abstract: BackgroundPorphyromonas gingivalis is a gram-negative bacterium that causes destructive chronic periodontitis. In addition, this bacterium is also involved in the development of cardiovascular disease. The aim of this study was to investigate the effects of P. gingivalis infection on gene and protein expression in human aortic smooth muscle cells (AoSMCs) and its relation to cellular function.ResultsAoSMCs were exposed to viable P. gingivalis for 24 h, whereafter confocal fluorescence microscopy was used to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 49 publications
(45 reference statements)
0
27
0
Order By: Relevance
“…Our data complement recent investigations, which applied microarray technology and different cell types, stimuli and exposure durations. [48][49][50] For instance, Yu et al investigated human macrophages isolated from buffy coats that were challenged with 10 mg/ml LPS or live Pg for 2 h. 48 The authors detected 575 differentially regulated genes in the LPS group based on three independent macrophage experiments, and identified 13 pathways, most of which correspond to host immune defense. 48 The present study identified >900 genes, >2149 upstream regulators and 200 canonical pathways implicated in the Pg-induced immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Our data complement recent investigations, which applied microarray technology and different cell types, stimuli and exposure durations. [48][49][50] For instance, Yu et al investigated human macrophages isolated from buffy coats that were challenged with 10 mg/ml LPS or live Pg for 2 h. 48 The authors detected 575 differentially regulated genes in the LPS group based on three independent macrophage experiments, and identified 13 pathways, most of which correspond to host immune defense. 48 The present study identified >900 genes, >2149 upstream regulators and 200 canonical pathways implicated in the Pg-induced immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence shows the M1 phenotype macrophages are the main source in NOTCH molecules in RA and play an important role in the chronicity of synovial inflammation . On the other hand, P. gingivalis infection increases NOTCH signaling in aortic smooth muscle . It is plausible that by a similar mechanism of NOTCH signaling, periodontal bacteria may aggravate the inflammatory process in RA.…”
Section: Discussionmentioning
confidence: 99%
“…63,64 On the other hand, P. gingivalis infection increases NOTCH signaling in aortic smooth muscle. 65 It is plausible that by a similar mechanism of NOTCH signaling, periodontal bacteria may aggravate the inflammatory process in RA. immune responses.…”
Section: Rel Gene Is a Proto-oncogene Associated With B-cell T-cell mentioning
confidence: 99%
“…In correla tion, interaction between P. gingivalis and human blood cells, for example, platelets, neutro phils, monocytes, and T-cells, is mainly mediated by TLR2 and has dramatic inflammatory and immunomodulatory effects, including cellular aggregation, oxygen radical production, lowdensity lipoprotein (LDL) oxidation, and release and degradation of cytokines. Furthermore, P. gingivalis changes the expression of more than thousand genes in vascular smooth muscle cells [84]. For example, P. gingivalis upregulates genes involved in proliferation, for example, the TGFβ1 pathway and production of matrix proteins, but downregulates pro-inflammatory genes, such as those involved in IL-1β, IL-6, and CXCL8 production.…”
Section: Periodontitis Systemic Inflammation and Cardiovascular Dismentioning
confidence: 99%